Voxel-Mirrored Homotopic Connectivity Associated With Change of Cognitive Function in Chronic Pontine Stroke - Wu, Luobing; Wang, Caihong; Liu, Jingchun; Guo, Jun; Wei, Ying; Wang, Kaiyu; Miao, Peifang; Wang, Yingying; Cheng, Jingliang (Frontiers in Aging Neuroscience, 2021)
Cognitive function impairment after infarction is a commonly accepted reality. In addition, the research on cognitive function has attracted much attention nowadays. There is still a large space for cognitive opinions, and no one seems to have explored the influence of inter-hemispheric homotopic information exchange on cognitive function. This study attempts to explore this blank space. Fifty-six patients with onset chronic pontine stroke (28 left-sided stroke (LP) and 28 right-sided stroke (RP)) and 35 matched healthy controls (HC) underwent functional magnetic resonance imaging and behavioral assessments of cognitive function. One-way ANOVA analysis was performed for the three groups（the HC, the LP and the RP）with voxel-mirrored homotopic connectivity (VMHC). Results showed that there were significant decreases in bilateral lingual gurus (Lingual_L and Lingual_R) and left precuneus (Precuneus_L). Post hoc multiple comparisons showed a significant difference between the RP and the HC. Moreover, we explored the relationship between z-values of the significantly different clusters in VMHC and the behavior-task scores by using Pearson correlation, and found that both scores of short-term memory and long-term memory in Rey Auditory Verbal Learning Test were positively correlated with z-values of Lingual_L, Lingual_R and Precuneus_L in VMHC. Besides that, z-values of Precuneus_L in VMHC was also found negatively correlated with reaction time for correct responses of Flanker task, of digital_1_back task and spatial_1_back task. In conclusion, first, that right hemisphere offered more contribution in rusults this study; Second, lingual gurus showed a important pole in semantic processing and then affected verbal memory; Third, the precuneus influenced the working memory no matter in auditory vebal or visual term. This study provides a perspective for us to recognize the cognitive impairment after stroke.